The Resistance Mechanisms of Anilinopyrimidine Fungicide Pyrimethanil in Sclerotinia sclerotiorum - Yanfen Wang; Zeyuan Chen; Tiancheng Liu; Xupeng Gao; Yanchao Shi; Honghui Wu; Runqiang Liu; Yunchao Kan; Hao Yu; Feng Zhou (Journal of Fungi)
The necrotrophic pathogen Sclerotinia sclerotiorum is widely distributed and infects a broad range of hosts, making it one of the most economically damaging plant pathogens. This study demonstrated that pyrimethanil, an anilinopyrimidine fungicide, exhibited potent activity against S. sclerotiorum, with EC50 values ranging from 0.411 to 0.610 μg/mL. Four highly pyrimethanil-resistant mutants were obtained through chemical taming, with EC50 values of 7.247 to 24.718 μg/mL. These mutants exhibited significantly reduced mycelial growth, sclerotia production, and pathogenicity compared to their wild-type parental isolates, indicating that pyrimethanil resistance suffered a fitness penalty in S. sclerotiorum. Notably, three mutants (DDJH-Pyri-R1, DDJH-Pyri-R3, and DDJH-Pyri-R4), completely lose the capacity to infect detached tomato leaves. Point mutations that cause amino acid changes in the predicted sequence of cystathione-γ synthase (CGS) and cystathione-β lyase (CBL), encoded by SsCGS1 and SsCGS2, were identified in three mutants. However, one mutant (DDJH-Pyri-R2) showed no mutations in these genes, suggesting an alternative resistance mechanism. Molecular docking revealed that mutations in SsCGS1-R3, SsCGS1-R4, and SsCGS2-R1 reduced the binding affinity between pyrimethanil and SsCGSs. No cross-resistance was observed between pyrimethanil and other commonly used fungicides, including carbendazim, fludioxonil, prochloraz, tebuconazole, pyraclostrobin, boscalid, fluazinam, and cyprodinil. These findings provide valuable insights for designing resistance inhibitors and suggest that pyrimethanil has significant potential for controlling soybean sclerotinia stem rot (SSR) caused by S. sclerotiorum.